Etika Periklanan pada Promosi Judi Online oleh Konten Hiburan di Instagram - Maura Azzakiyah Basya; Dinda Rizqia Maulana; Annabilla Zahra; Daniel Handoko (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Social media has become a strategic space in the digital advertisin landscape including for illegal promotions such as online gambling. This study discusses covert advertising practices by entertainment accounts on Instagram that subtly promote gambling websites through watermarks, without disclosing that the content is sponsored. such practices are considered unethical and misleading, particularly for young audiences. this research uses a qualitative descriptive approach through literature review and content observation. the findings reveal that the lack of oversight and ethical awareness among content creators opens opportunities for misuse of social media as a platform for prohibited promotions. additionally, the absence of advertising labels makes it difficult for audiences to distinguish between entertainment and promotion. this study highlights the need for ethical advertising education among content creators, along with stricter regulations and monitoring by relevant authorities. by doing so, unethical and illegal advertising practices can be prevented, protecting the broader public, especially the younger generation, who are highly active on social media.